2004
DOI: 10.1159/000081354
|View full text |Cite
|
Sign up to set email alerts
|

In situ Characterization of Gonadotropin- Releasing Hormone-I, -III, and Glutamic Acid Decarboxylase Expression in the Brain of the Sea Lamprey, <i>Petromyzon marinus</i>

Abstract: The distribution of lamprey gonadotropin-releasing hormone (GnRH)-I and -III has been extensively characterized by immunocytochemistry in the forebrain of the sea lamprey, Petromyzon marinus. However, the cellular location of lamprey GnRH-III mRNA expression by in situ hybridization in the lamprey brain has not been determined. We show for the first time the location of expression of lamprey GnRH-III, as well as provide a more comprehensive in situ study of lamprey GnRH-I and glutamic acid decarboxylase (GAD; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 76 publications
6
18
0
Order By: Relevance
“…Lamprey GnRH immunoreactive nerve fibers originate from cells in the arc-shaped hypothalamic/preoptic areas and end at the neurohypophysis forming the preoptico-hypophyseal GnRH tract (24, 26). The same pattern restricted to the preoptic/hypothalamic area was found by in situ experiments for lGnRH-I and -III transcripts (27). Presence of GnRH-II transcripts in the olfactory bulb and in the hindbrain in addition to hypothalamus suggested by in situ experiments were not confirmed by immunohistochemistry (24).…”
Section: Lamprey Gnrh Systemsupporting
confidence: 77%
“…Lamprey GnRH immunoreactive nerve fibers originate from cells in the arc-shaped hypothalamic/preoptic areas and end at the neurohypophysis forming the preoptico-hypophyseal GnRH tract (24, 26). The same pattern restricted to the preoptic/hypothalamic area was found by in situ experiments for lGnRH-I and -III transcripts (27). Presence of GnRH-II transcripts in the olfactory bulb and in the hindbrain in addition to hypothalamus suggested by in situ experiments were not confirmed by immunohistochemistry (24).…”
Section: Lamprey Gnrh Systemsupporting
confidence: 77%
“…The chapter contains an extensive list of the localisation of neurotransmitters and other neuronal substances in the lamprey brain. More recent data on brain neurochemical distribution, proliferation and connectivity, or data not mentioned in this list, include the work of (Abalo et al 2005;Auclair et al 2004;de Arriba Mdel and Pombal 2007;de Miguel et al 1990;Del Carmen De Andres et al 2002;Frontini et al 2003;Gonzalez et al 1999;Laframboise et al 2007;Melendez-Ferro et al 2002a, 2002bMenard et al 2007;Osorio et al 2006;PerezCostas et al 2002PerezCostas et al , 2004Pflieger and Dubuc 2004;PierreSimons et al 2002;Pombal et al 1997aPombal et al , 1997bPombal et al , 2001Robertson et al 2006Robertson et al , 2007Root et al 2005;Vidal Pizarro et al 2004;Villar-Cheda et al 2002, 2006Weigle and Northcutt 1999). Neuronal phenotype distribution and fibre connectivity in the lamprey brain have also been reviewed by Wullimann and Vernier (2006).…”
Section: The Lamprey Brain: Adult Featuresmentioning
confidence: 99%
“…However, it is unclear if the E2–GnRH interaction in lamprey occurs through a direct or an indirect mechanism. Within the preoptic anterior hypothalamus, co-localization studies of GABA and GnRH in lamprey have indicated GABA and GnRH-containing cells are closely associated (Reed et al, 2002; Root et al, 2005), supporting the possibility of a GABA-mediated (indirect) mechanism of E2–GnRH interaction in lamprey.…”
Section: Introductionmentioning
confidence: 96%
“…In some teleosts, those neurohormones/factors include dopamine, neuropeptide Y, gamma-aminobutyric acid (GABA), and more recently gonadotropin-inhibitory hormone (GnIH) and kisspeptin (KiSS; Kah and Dufour, 2010). In lampreys, GABA and neuropeptide Y have been shown to be involved with brain GnRH and reproduction (Conlon et al, 1994; Root et al, 2004, 2005). Glutamic acid decarboxylase (GAD; GABA-synthesizing enzyme) mRNA was expressed in four distinct cell populations in the lamprey brain, ranging from the telencephalon and diencephalon of the forebrain to the mesencephalon and rhombencephalon of the midbrain and hindbrain in adult lamprey (Root et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation